A CEGAR Scheme for Information Flow Analysis - Töws, Manuel; Wehrheim, Heike (Proceedings of the 18th International Conference on Formal Engineering Methods (ICFEM 2016))
Information flow analysis studies the flow of data between program entities (e.g. variables), where the allowed flow is specified via security policies. Typical information flow analyses compute a conservative (over-)approximation of the flows in a program. Such an analysis may thus signal non-existing violations of the security policy.In this paper, we propose a new technique for inspecting the reported violations (counterexamples) for spuriousity. Similar to counterexample-guided-abstraction-refinement (CEGAR) in software verification, we use the result of this inspection to improve the next round of the analysis. We prove soundness of this scheme.

Einsatz- und Nutzenpotentiale von Augmented Reality im Kontext von Industrie 4.0 - Röltgen, Daniel; Anacker, Harald; Dumitrescu, Roman (VDE Kongress 2016 Internet of Things, Mannheim, Deutschland, 7. - 8. Nov. 2016)

Einsatz von Leuchten zur Standortbestimmung in der Produktion - Falkowski, Tommy; Fechtelpeter, Christian; Peitz, Christoph; Kühn, Arno; Dumitrescu, Roman (VDE Kongress 2016, 7. - 8. Nov. 2016)

Reference Architecture and Maturity Levels for Cyber-Physical Systems - Westermann, Matthias; Anacker, Harald; Dumitrescu, Roman; Czaja, Anja Maria (2nd IEEE International Symposium on Systems Engineering 2016, Edinburgh, Scotland, 4. - 5. Okt. 2016)

Reliability in MID - barriers, potentials, fields of action - Fechtelpeter, Christian; Jürgenhake, Christoph; Dumitrescu, Roman; Mager, Thomas; Fritz, Karl-Peter; Grötzinger, Tobias; Müller, Hagen; Wild, Paul; Zimmermann, Andre (12th International Congress on Molded Interconnect Devices, Conference Proceedings , 28. - 30. Sep. 2016)

Classification of MID-prototypes - Jürgenhake, Christoph; Falkowski, Tommy; Dumitrescu, Roman (12th International Congress on Molded Interconnect Devices, Würzburg, 28. - 30. Sep. 2016)

Systematic for function-oriented development of spatial integrated circuit carriers - Jürgenhake, Christoph; Dumitrescu, Roman (International Design Conference - Design 2016, 16. - 19. Mai 2016)

Exhaustiveness of Systems Structures in Model-Based Systems Engineering for Mechatronic Systems - Kaiser, Lydia; Bremer, Christian; Dumitrescu, Roman (Sysint - 3rd International Conference on System-Integrated Intelligence: New Challenges for Product and Production Engineering)

Function-based feasibility study and benchmark for MID concepts - Jürgenhake, Christoph; Falkowski, Tommy; Fechtelpeter, Christian; Dumitrescu, Roman (Sysint - 3rd International Conference on System-Integrated Intelligence: New Challenges for Product and Production Engineering)

A concept for managing information in early stages of product engineering by integrating MBSE and workflow management systems - Bretz, Lukas Helmut; Tschirner, Christian; Dumitrescu, Roman (IEEE ISSE: Proceedings of 2016 International Symposium on Systems Engineering)